Meeting the funding gap in urban local authorities in Zimbabwe: a case study of Gweru city council - Mamboko, Patrick; Tsokota, Theo; Giyane, Maximillan; Mhaka, Charity (A Global Society for Multidisciplinary Research, 2019)
The decentralization of local authorities in Zimbabwe has resulted in local authorities being thrown to the deep end in terms of meeting societal needs. The ever increasing population coupled with the financial crisis both on the global stage and at local level makes it difficult for Zimbabwean local authorities to continue relying on traditional sources of finance for service delivery, sustainability and social development. The aim of the study was to explore alternative financing options and to gain an insight into administrative and legal systems that negate Gweru City Council’s revenue mobilization strategies. The data was collected using document review and follow up interviews with the Treasury personnel. It was noted that the legal and administrative systems were major impediments in the quest for local authority to boost its revenue base. This calls for the expansion of existing revenue sources and development of a policy framework which encourages Public-Private Partnerships.